Analisis Perilaku Pemesanan Kembali Kamar Hotel di Aplikasi Travel Menggunakan Model Theory of Reasoned Action - Erlina, Erlina; Deli, Deli (STMIK Banjarbaru, 2023)
The hotel industry is a global industry that has shown its development in the business world. One of these developments comes from technology that replaces conventional business models with Online Travel Agencies (OTAs). It is imperative for OTA companies to prioritize delivering high-quality services to their user base. The aim the research is to determine impact of TRA in booking hotel rooms by OTA users by comparing the Traveloka and Tiket.com applications. This research uses a quantitative and qualitative approach by distributing questionnaires then tested using the SPSS v25 and AMOS applications. The research population comprises individuals from generation Y in Batam, aged between 27 and 42 years who have used Traveloka or Tiket.com applications. The research findings reveal that E-Satisfaction, Ease of Use, E-Trust influence Online Repurchase Intention, E-Service Quality does not influence Online Repurchase Intention, and E-Trust influences E-Satisfaction in both applications. Ease of Use affects E-Satisfaction in Traveloka, but has no effect for Tiket.com. E-Service Quality affects E-Satisfaction for Tiket.com, but has no effect for Traveloka.Keywords: Application; Online Travel Agent; Hospitality; Theory of Reasoned ActionÂ AbstrakIndustri perhotelan merupakan salah satu industri global yang telah menunjukkan perkembangannya dalam dunia bisnis. Salah satu perkembangan tersebut berasal dari teknologi yang menggantikan model bisnis konvensional dengan Online Travel Agencies (OTAs). Perusahaan OTA perlu memperhatikan kualitas pelayanan kepada pengguna. Penelitian ini ditujukan untuk mengidentifikasi pengaruh TRA dalam reservasi hotel oleh pengguna OTA dengan perbandingan aplikasi Traveloka dan Tiket.com. Pendekatan penelitian ini mencakup kualitatif dan kuantitatif, yaitu menyebarkan survei dan diuji menggunakan aplikasi SPSS v25 dan AMOS. Populasi penelitian ini adalah generasi Y di Kota Batam dengan rentang usia 27-42 tahun yang pernah mengakses aplikasi Traveloka atau Tiket.com. Temuan penelitian mengungkapkan bahwa E-Satisfaction, Ease of Use, E-Trust mempengaruhi Online Repurchase Intention, E-Service Quality tidak mempengaruhi Online Repurchase Intention, serta E-Trust mempengaruhi E-Satisfaction untuk kedua aplikasi tersebut. Ease of Use mempengaruhi E-Satisfaction untuk Traveloka, tetapi tidak berpengaruh untuk Tiket.com. E-Service Quality mempengaruhi E-Satisfaction untuk Tiket.com, tetapi tidak berpengaruh untuk Traveloka.Â